Analisis Penerapan Perencanaan Pajak Melalui Metode Penyusutan dan Revaluasi Aset tetap sebagai Upaya Penghematan Pembayaran Pajak Penghasilan Badan pada PT Chitra Kalpika Mas - Mitha Ramadhani; Muhammad Arief; Rizki Filhayati Rambe (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine whether the application of tax planning through the depreciation method and fixed asset revaluation can save the payments of corporate income tax at PT Chitra Kalpika Mas. The analysis process used is quantitative descriptive analysis, which starts with data collection, describes and then is interpreted for further analysis and is used as a reference in determining the effectiveness of planning in an effort to save on corporate income tax payments.Based on the research result obtained, it shows that the application of tax planning through the depreciation method can save the payment of corporate income tax at PT Chitra Kalpika Mas. While for the implementation of tax planning through revaluation of fixed assets has not been said to be successful in saving payment of corporate income tax at PT Chitra Kalpika Mas, due to the Final PPh that must be paid by the company as a result of revaluing fixed assets.